A Framework for Storage and Retrieval of Distributed Vector Graphics Objects - B. Vijayakumar, K. Nithya, Amartya Das Sharma (International Journal of Advanced Science and Technology, 2020)
Vector Graphical Objects play an important role in many image processing applications such as web, mobile authoring, printing and GIS mapping. These objects are stored in various formats such as scalable vector graphics, postscript, portable document format and adobe illustrator artwork. These objects are stored at one or more sites in the internet or a local area network. Hence, it is essential to have a framework for storing and retrieving these objects in an organized manner. The present work proposes a framework for efficient storage and retrieval of vector graphical objects in a distributed environment, using content and/or metadata. It comprises of a control site and many other sites from where the users can initiate queries for execution. The control site comprises of distributed query execution manager and query results aggregator. The users can submit queries on any vector graphic object, based on its content and/or metadata. The global query analyzer at the control site parses the input query and sets it up for execution by distributed query execution manager. The allocation schema provides information on distribution of data. The sub queries run in parallel at different sites. The aggregator combines, the output SVG objects and transfers them to the users at the query initiation sites. This framework provides both flexibility and scalability in the management of distributed vector graphical objects.